2020
DOI: 10.14778/3389133.3389145
|View full text |Cite
|
Sign up to set email alerts
|

Single machine graph analytics on massive datasets using Intel optane DC persistent memory

Abstract: Intel Optane DC Persistent Memory (Optane PMM) is a new kind of byte-addressable memory with higher density and lower cost than DRAM. This enables the design of affordable systems that support up to 6TB of randomly accessible memory. In this paper, we present key runtime and algorithmic principles to consider when performing graph analytics on extreme-scale graphs on Optane PMM and highlight principles that can apply to graph analytics on all large-memory platforms. To demonstrate the importance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The results show that WarpX-PM has the lowest inter-socket traffic (close to zero). Memory mode is not NUMA-aware and cannot cache accesses to remote PM in a local DRAM [9]. The NUMA first touch policy is NUMA-aware, but data may be distributed to remote DRAM when the local DRAM is exhausted.…”
Section: Evaluation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that WarpX-PM has the lowest inter-socket traffic (close to zero). Memory mode is not NUMA-aware and cannot cache accesses to remote PM in a local DRAM [9]. The NUMA first touch policy is NUMA-aware, but data may be distributed to remote DRAM when the local DRAM is exhausted.…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…Database and graph workloads. Recent works also propose various performance optimizations of databases and graph workloads on the Optane PM [5,9,15,17,30,43]. Yang et.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…RAMinate [22], Heteros [24], Yan et al [82] propose the state-of-the-art memory management solutions for general purpose which guides page placement based on an existing Linux page replacement mechanism. Application-specific HM management solutions [8,11,13,18,33,35,45,47,75,78,79,85] leverage domain knowledge to further improve performance. MyNVM [13] proposes a software-managed multi-level caches policy to treat DRAM and NVM as caches for hard drives.…”
Section: Related Workmentioning
confidence: 99%
“…We are evaluating Optane DC for different streams that we encounter in different HPC applications and focus on using Optane DC as an extended address space for the same. Gill et al [7] used the Optane DC PMM to evaluate shared-memory graph frameworks like Galois on real world web-crawls. They found that Optane DC PMM yields performance and cost benefit for massive graph analytics when compared to a distributed graph frameworks on existing production clusters.…”
Section: Related Workmentioning
confidence: 99%